PENGARUH ESG, CAPITAL INTENSITY DAN THIN CAPITALIZATION TERHADAP AGRESIVITAS PAJAK - Wardani, Ruly Alifah; Hidayati, Wahyu Nurul (LPPM Universitas Ibnu Sina, 2025)
Abstrak The government's goal of maximizing tax sector revenue is at odds with the company's goal of maximizing its profits. This research aims to prove the effect of ESG, Capital Intensity, and Thin Capitalization on Tax Aggressiveness with an empirical study of LQ-45 companies listed on the Indonesia Stock Exchange for the period 2018-2022. The method used is a quantitative method. The population of this study is LQ-45 sector companies listed on the Indonesia Stock Exchange. The collection method used in this study is purposive sampling. With the purposive sampling method, the number of companies sampled was 6 (six) companies out of 45 companies with an observation period of 5 (five) years, namely 2018 to 2022. The results of the t-hypothesis test study obtained that ESG had no significant effect on tax aggressiveness. Capital intensity has no significant effect on tax aggressiveness. Thin capitalization has a significant effect on tax aggressiveness. there is a significant simultaneous influence between ESG, capital intensity, and thin capitalization on tax aggressiveness in LQ-45 companies in 2018-2022. Kata kunci: ESG, Capital Intensity, Thin Capitalization and Tax Aggressiveness